Visualization of Hair Bulbs through the Scalp: A Trichoscopic Feature of Erosive Pustular Dermatitis of the Scalp - Starace, Michela (Int J Trichology, 2016)
Erosive pustular dermatitis of the scalp (EPDS) typically affects elderly people with scarring alopecia. Videodermoscopy (VD) of the scalp has never been assessed in the diagnosis of EPDS. To evaluate the trichoscopy features of EPDS, we carried out a retrospective analysis of VD images obtained in the scalp of ten patients who affected by EPDS and were compared with those obtained from a series of thirty patients who affected by other type of scarring alopecia. The most specific VD feature was thus represented by evident hair bulb in the scarring scalp, observed in all patients.